Effects of probiotic supplementation on immune and inflammatory markers in athletes: a meta-analysis of randomized clinical trials - Guo, Y.-T.; Peng, Y.-C.; Yen, H.-Y.; Wu, J.-C.; Hou, W.-H. (Medicina, 2022)
Background and Objectives: Probiotic supplementation can prevent and alleviate gastrointestinal and respiratory tract infections in healthy individuals. Markers released from the site of inflammation are involved in the response to infection or tissue injury. Therefore, we measured the pre-exercise and postexercise levels of inflammation-related markers—tumor necrosis factor (TNF)-a, interleukin (IL)-6, IL-8, IL-10, interferon (IFN)-gamma, salivary immunoglobulin A (IgA), IL-1ß, IL-2, IL-4, and C-reactive protein (CRP)—in probiotic versus placebo groups to investigate the effects of probiotics on these markers in athletes. Probiotics contained multiple species (e.g., Bacillus subtilis, Bifidobacterium bifidum, etc.).